Bioinformatic Study of the Active Compound of Morusin in Mulberry (Morus alba) against Breast Cancer - Sarmoko Sarmoko; Afif Hariawan Pratama; Nur Amalia Choironi; Muhammad Salman Fareza (Indonesian Journal of Cancer Chemoprevention, 2023)
Morusin, an active constituent of the mulberry plant (Morus alba), exhibits inhibitory effects on several types of cancer cells in vitro, including breast cancer. This study aimed to identify potential target proteins of morusin, investigate the binding energy, and explore type of interactions between morusin and the target protein. Morusin target was searched using the PubMed, STITCH, STRING, and Cytoscape databases. Subsequently, the obtained morusin target protein data underwent processing using Autodock Tools and DS BIOVIA to facilate the simulation of molecular docking between morusin and the target protein. The study identified EGFR, SRC, and MAPK1 as potential targets for morusin. Docking simulations revealed that both EGFR and SRC represent viable targets for morusin, as their binding energies were lower than those of the native ligand and lapatinib. Specifically, the bond energies at EGFR were -9.6, -7.5, and -9.2 kcal/mol for morusin, the native ligand, and lapatinib, respectively. Similarly, at SRC, the corresponding bond energies were -8.2, -6.4, and -5.3 kcal/mol. Morusin demonstrated binding interactions with Leu694, Val702, Leu820, Ala719, Leu768, and Lys721 at the active site of EGFR, and with Lys295 and Gly344 at the binding active sites of SRC. Consequently, morusin has the potential to suppress cancer cell growth by targeting EGFR and SRC.Keywords: cancer cells, EGFR and SRC as targets, molecular docking, morusin, mulberry plant.